2020
DOI: 10.5430/jnep.v10n12p38
|View full text |Cite
|
Sign up to set email alerts
|

Adult cancer patients’ barriers toward pain management: A literature review

Abstract: Background and objective: Cancer pain is the most common symptom among cancer patients. Despite strategies to control cancer pain, cancer patients’ beliefs and attitudes influence the effectiveness of cancer pain management. The aim of this literature review was to identify and explore adult cancer patients’ barriers toward pain management.Methods: A literature review was conducted. CINAHL, Medline, and PsychINFO databases were searched for relevant articles from 2008 to 2019. Twenty one articles were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For instance, many patients and their caregivers believed that the Qur’an and the prayers could cure diseases, such as cancer, and relieve physical suffering like pain (Erol et al, 2018 ; Hatamipour et al, 2015 ; Hosseini et al, 2016 ; Makhlouf et al, 2020 ). Thus, some patients and their caregivers usually prefer to use the Qur'an and prayers instead of medical medications to help the patients cope with their disease, anxiety, and pain (Ibrahim et al, 2020 ; Pathmawathi et al, 2015 ). Our recent systematic review found that patients’ and caregivers’ perceptions of cancer pain and opioids are influenced by their religious and cultural beliefs (Makhlouf et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many patients and their caregivers believed that the Qur’an and the prayers could cure diseases, such as cancer, and relieve physical suffering like pain (Erol et al, 2018 ; Hatamipour et al, 2015 ; Hosseini et al, 2016 ; Makhlouf et al, 2020 ). Thus, some patients and their caregivers usually prefer to use the Qur'an and prayers instead of medical medications to help the patients cope with their disease, anxiety, and pain (Ibrahim et al, 2020 ; Pathmawathi et al, 2015 ). Our recent systematic review found that patients’ and caregivers’ perceptions of cancer pain and opioids are influenced by their religious and cultural beliefs (Makhlouf et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%